Custo de oportunidade no binômio saúde e esgotamento sanitário: proposta de um modelo de avaliação com custo-benefício utilizando dados governamentais - Soares, Mara Alves (2017)
Research has shown the importance of basic sanitation in preventing morbidity and mortality. Among the economic evaluations capable of reflecting the cost of opportunity, when presenting the sacrifice of one alternative in favor of another, the techniques of evaluation as cost-benefit are presented as preferred by the researchers. The opportunity cost reflects the benefits gained by society with the best use of these resources. The present study aimed to propose a cost-effective evaluation model, using government data, to evaluate the cost of opportunity in the health and sanitary sewage binomial. From the bibliographic review, it was possible to know the specificities of each sector in relation to the survey of costs. Data collection was done by the Department of Information Technology of the Brazilian National Health System (DATASUS), the Brazilian Institute of Geography and Statistics (IBGE), the Institute of Applied Economic Research (IPEADATA) and the National Sanitation Information System (SNIS) . The methodological procedures of the research were divided into health and sanitary sewage, in spite of both using cost-benefit, and were subsequently observed jointly to express the opportunity cost. The municipality of Monte Carmelo served as an example to demonstrate the various calculations, both health and sanitary sewage, and the applicability and understanding of the opportunity cost evaluation model. The programming environment was developed using the Java language with Software Development Kit (SDK) version 1.7 in the Java Enterprise Edition (JAVA EE) platform, and the use code is not free. The results show that the model reflects the cost of opportunity in the health and sanitation binomial and allows a certain flexibility in alternatives and / or simulations that allow the support of public managers with information regarding the challenges and potentiality of a decision.